2018
DOI: 10.14222/turkiyat3991
|View full text |Cite
|
Sign up to set email alerts
|

2018 Türkçe Dersi̇ Öğreti̇m Programindaki̇ Kazanimlarin Üst Düzey Düşünme Beceri̇ler

Abstract: az olduğu tespit edilmiştir. Kazanımlardaki üst düzey düşünme becerilerinin dağılımı da anlama ve anlatma becerileri açısından yine farklılık göstermektedir.understand and explain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 4 publications
0
2
0
15
Order By: Relevance
“…This finding can be interpreted as the great majority of the objectives in the 5th-8th grades are in the lower level knowledge stages. Söylemez (2018) concluded that a considerable place is allocated to critical thinking skills in the objectives related to listening and reading skills while a very small place is allocated to these skills in the objectives related to speaking and writing skills. In the study conducted by Yeşilpınar (2011) on elementary school teachers and preservice teachers, it was found that the majority of the elementary school teachers think that activities should be conducted to teach critical thinking skills in curriculums and that they experience difficulties stemming from the curriculum, environment and family in the implementation of these activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding can be interpreted as the great majority of the objectives in the 5th-8th grades are in the lower level knowledge stages. Söylemez (2018) concluded that a considerable place is allocated to critical thinking skills in the objectives related to listening and reading skills while a very small place is allocated to these skills in the objectives related to speaking and writing skills. In the study conducted by Yeşilpınar (2011) on elementary school teachers and preservice teachers, it was found that the majority of the elementary school teachers think that activities should be conducted to teach critical thinking skills in curriculums and that they experience difficulties stemming from the curriculum, environment and family in the implementation of these activities.…”
Section: Discussionmentioning
confidence: 99%
“…When the recent research on Turkish Course Curriculum and critical thinking are examined, it is seen that the objectives of the 2018 Turkish Course Curriculum are evaluated according to higher-order thinking skills (Söylemez, 2018;Ünveren Kapanadze, 2019) and the revised Bloom taxonomy (Çerçi, 2018;Büyükalan Filiz, Yıldırım, 2019). In the study conducted by Söylemez (2018), all of the listening, speaking, reading and writing objectives for the 4th-8th grades of the 2018 Turkish Course Curriculum were examined according to higher-order thinking skills. In the study, in which critical thinking, reflective thinking and problem solving were determined as higher-order thinking skills, the collected data were descriptively analyzed by the researcher and a field expert.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yapılan bazı araştırmalar bu sonucu desteklemektedir. Söylemez (2018) yaptığı çalışmada eleştirel, yansıtıcı, yaratıcı düşünme ve problem çözme gibi üst düzey düşünme becerilerine yönelik 2018 Türkçe dersi öğretim programında yer alan temel dil becerilerine ait kazanımların belirlendiğini belirtmiştir. Bu araştırmada öğretmen görüşlerine göre öğrenciler tarafından yapılan bireysel etkinliklerin ve grup etkinliklerinin öğrencilerin eleştirel, yansıtıcı, yaratıcı düşünme becerileri ile problem çözme becerilerini destekler nitelikte olduğu belirtilebilir.…”
Section: Sonuç Tartışma Ve öNerilerunclassified
“…Alan yazın incelendiğinde, 2018 yılı Türkçe dersi öğretim programının incelendiği, değerlendirildiği ve önceki programlarla karşılaştırıldığı (Aslan ve Atik, 2018;Aydın, 2017;Aydın ve Sadioğlu, 2018;Bağcı-Ayrancı ve Mutlu, 2017;Bağcı-Ayrancı ve Pilav, 2017;Bıçak ve Alver, 2018;Çerçi, 2018;Çevik ve Güneş, 2017;Eken ve Öksüz, 2019;Koçoğlu ve Yanpar-Yelken, 2018;Konuk, 2018;Ömeroğlu, 2018;Özcan ve Yıldız, 2018;Özenç, 2018;Söylemez, 2018;Susar-Kırmızı ve Yurdakal, 2019) görülmüştür. Ayrıca yetkinlikler, öğrenmeyi öğrenme ve yaşam boyu öğrenme alanlarında (Akın, Çıray ve Sönmez, 2013;Çerçi, 2005;Direkçi, Akbulut ve Şimşek, 2019;Ekmen ve Bakar, 2018;Mercan, 2011;Pınarcık, Danacı, Deniz ve Eran, 2016) çalışmalara rastlanmıştır.…”
Section: Introductionunclassified
“…Öğrencilerin dil becerileriyle birlikte düşünme becerilerin geliştirilmesi de Türkçe derslerinin temel hedefleri içerisinde yer almaktadır (MEB, 2019). Bu anlamda Türkçe dersi öğretim programlarında öğrencilerin eleştirel, yaratıcı, yansıtıcı, analitik düşünme gibi üst düzey düşünme becerileri ile problem çözme, akıl yürütme, bilimsel düşünme gibi potansiyellerinin geliştirilmesine yönelik kazanımlar yer almaktadır (Söylemez, 2018). Böylelikle düşüncenin temel aracı olarak dil eğitiminde öğrencilerin üst düzey düşünme becerileri kazanmaları beklenmektedir.…”
Section: Introductionunclassified